GPX3 expression was down-regulated but positively correlated with poor outcome in human cancers - Hu, Qingyi; Chen, Jiaoshun; Yang, Wen; Xu, Ming; Zhou, Jun; Tan, Jie; Huang, Tao (Frontiers in Oncology, 2023)
Cancer is a crucial public health problem and one of the leading causes of death worldwide. Previous studies have suggested that GPX3, an extracellular glutathione peroxidase, may be involved in cancer metastasis, the main risk leading to cancer-related death and the most challenging obstacle to cancer treatment. However, how GPX3 affects cancer patient outcomes and the underlying mechanism remains unclear. We explored the relationship between GPX3 and clinical features, immune infiltration characteristics, migration and metastasis, and chemotherapy sensitivities of human cancers. We further investigated the potential genetic and epigenetic regulation of GPX3 in cancer. Our results suggested that GPX3 plays a complicated role in the tumor microenvironment (TME), simultaneously promoting metastasis and chemotherapy resistance in human cancers.